Análisis del tratamiento de las noticias de crónica roja caso diario extra, primer trimestre 2019 - Aponte Castro, Mirna Raquel (2020)
The purpose of this work was to analyze the treatment of the news of the Red Chronicle section of Diario Extra, published in the first quarter of 2019; For this, a “Case Study” was carried out because it allows us to investigate in depth the way in which this medium wrote and published the information of the events that took place during the period of that time. With the implementation of the new Organic Law of Communication, changes arose in the way of presenting the journalistic content; Therefore, Diario Extra, being a pioneer of this type of information, failed to comply with this legal framework, infringing on the deontological norms stipulated in article 10 of this normative body, since its news presents them sensationally. Finally, it was concluded that there is disrespect on the part of Diario Extra towards the Organic Law of Communication. This medium, on different occasions, has been sanctioned for the way in which it has presented certain cases of news that have caused astonishment or scandal using the morbidity as a resource. A survey was applied to teachers of the Social Communication degree at the Technical University of Babahoyo. In addition, 20 headlines of the most impressive news of the first quarter of the year 2019 were analyzed.